The Impact of Business Ethics Implementation on Customer Trust in Product and Service Innovation - Eko Riyanto Putra Daya; Selamet Riyadi (International Journal Labs, 2025)
This study aims to analyze the effect of business ethics implementation on customer trust through product and service innovation in the Indonesian aviation industry, focusing on Garuda Indonesia and Lion Air. The research problem addressed is how business ethics influence customer trust, as well as the role of product and service innovation in strengthening this influence. The method employed is a quantitative approach using Structural Equation Modeling – Partial Least Squares (SEM-PLS), which enables testing of causal relationships among variables. The results indicate that business ethics have a significant positive effect on product and service innovation, as well as on customer trust. Furthermore, product and service innovation serves as a mediator that strengthens the influence of business ethics on customer trust. The implications of these findings suggest that airlines need to enhance the implementation of business ethics in their operations, as this not only improves corporate reputation but also strengthens relationships with customers through ethically grounded innovation. This study provides insights for airline business strategies in building stronger customer loyalty.